Development of strategic management and its features in banks with foreign capital - Вовчак, Ольга Дмитрівна (Technology audit and production reserves, 2016)
In the article the existing scientific approaches are considered and the essence of the concept of «strategic management» and «strategic management of the bank» are generalized. Peculiarities of the process approach to forming strategic management and the contents of its stages and sequence their implementation in the bank are revealed. An expediency of using provisions of other approaches to the strategic management of the bank is argumented. Corporate strategy of the bank with foreign capital are generalized. By reasons need for strategic management, which include the emergence of new goals are achieved within the current strategy is not possible, the complexity of determining banks in modern conditions necessary changes and so on. Existing scientific approaches to determining strategy of bank management positions are considered and summarized, as its process of identifying key priorities of the bank and a certain type of management, aimed at forming the desired economic situation of a particular bank. The content of the stages of strategic management of the bank includes: implementation of strategic analysis, which involves an analysis of external and internal environment of the bank; definition of vision, mission and strategic goals of the bank; formation of strategic alternatives and selection of the best based on their assessment of economic prospects and profitability; develop a strategic plan based on the selection of one or more alternatives of the bank that can be used simultaneously or in combination and develop specific programs for implementation of the plan; approval and implementation of the strategy through effective use of modern management methods and tools; evaluation of the implementation strategy and possible changes in the strategic plan and develop a system of indicators, which using is the information base for decision-making. It is paid attention to the main factors and main trends underlying the development strategies of banks, which include deposit and credit policy, justifying mechanisms, principles and order of fundraising and possible directions of allocation of funds. It was found that depending on the choice of directions various strategies are implemented, different types of banks are organized, structure of assets and liabilities are formed, etc. Expediency synthesis of certain aspects of the system, target, process, functional, resource, behavioral, cost and marketing approaches in the implementation of strategic management in banks and tools for their implementation is proved. Approaches to the use of corporate strategy as the main strategy of the bank are considered, which reflects the objectives of the bank and internal changes that need to be taken to improve competitiveness and maintaining long-term competitive advantage of the bank, and presented as a «pyramid», which includes the following functional strategies: marketing, financial, IT and HR strategies.The characteristic consistency of corporate strategy PJSC «Raiffeisen Bank Aval» in the organizational structure is implemented principles of strategic management – functioning risk management department of the bank, which provides a strategic analysis of the banks. It is concluded that the study focused on the bank of the average consumer, ensuring lower costs for bank services. Bank protected its competitors price advantage. Its lower prices also mean that they are less sensitive than competitors to adverse external market conditions.